CONCENTRATIONS TEST OF METHANE GAS FROM SWAMP FORAGE SILAGE WITH IN VITRO METHOD - Sarno Sarno; Moh. Rasyid Ridho; Dwi Puspa Indriani; Harmida Harmida; Adelia Rizki Pancasari (BIOVALENTIA: Biological Research Journal, 2017)
Aims of this study to concentration test of methane gas from swamp forage silage with in vitro methods.This study used Completely Randomized Design with 3 treatments and each treatment consisted of 5 replications. The treatments used are as follows: P1 (100% kumpai tembaga grass (Hymenachne acutigluma)), P2 (50% kumpai tembaga grass (Hymenachne acutigluma) + 50% kemon air (Neptunia oleracea lour)), P3 (100% kemon air ( Neptunia oleracea lour)). The parameters observed N-Ammonia, total gas production, methane gas concentrations in vitro and VFA partially. The results of variance showed that treatment significantly different (P <0.05) with methane concentration  in vitro with highest gas concentration treatment of silage made from 50%  kumpai tembaga grass (Hymenachne acutigluma) and  50% kemon air (Neptunia oleracea lour).Keywords: Concentration, Methane, Silage Forage Swamp, In Vitro.